Cantus in Laudem Virginis: el oficio poético de Juan Gil de Zamora - Pérez Rodríguez, Estrella (2014)
Estudio del oficio poético sobre la Virgen, compuesto por el franciscano Juan Gil de Zamora, a petición del rey Alfonso X el Sabio y dedicado a él. La autora determina su pertenencia al cursus catedralicio y analiza los cantos que componen sus dos horas litúrgicas: maitines y laudes, en su aspecto for
This paper studies the versified office of the Virgin, written by the grey friar Juan Gil from Zamora at the request of the king Alfonso X, and devoted to him. The author establishes that Gil’s office follows the Roman and secular use, and analyzes the formal aspect, the contents, the style and sources of the chants of its two liturgical hours: matins and lauds. She also examines some textual problems of its unique copy
Keywords: Gil de Zamora, Juan -- (O.F.M.); Poesía lírica